DEKONSTRUKSI HUSEN MUHAHAMMAD TEHADAP KONSEPSI KEPEMIMPINAN WANITA - M. Toha, Fahmi Rusdi (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
The results showed that according to Hussein Muhammad, women can become leaders based on considerations of benefit not for gender reasons. The success and failure of leadership is not caused by gender but through the means of democratic and constitutional leadership, as well as the protection of human rights, not tyrannical, authoritarian and centralistic power. Therefore, the Quranic verses and the hadith of the prophet that are